2016
DOI: 10.3389/fmicb.2016.01416
|View full text |Cite
|
Sign up to set email alerts
|

The Probiotic Butyricicoccus pullicaecorum Reduces Feed Conversion and Protects from Potentially Harmful Intestinal Microorganisms and Necrotic Enteritis in Broilers

Abstract: Probiotics which do not result in the development and spread of microbial resistance are among the candidate replacements for antibiotics previously used as growth promotors. In this study the effect of in-feed supplementation of the butyrate producing Butyricicoccus pullicaecorum strain 25-3T on performance, intestinal microbiota and prevention of necrotic enteritis (NE), a disease caused by Clostridium perfringens was evaluated in broilers. For the performance study, day old Ross 308 chicks were randomly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 53 publications
4
89
1
1
Order By: Relevance
“…Members of the genus Butyricicoccus are tolerant to changing intestinal conditions, produce butyrate, and have probiotic potential (57,58). In addition, Butyricicoccus is known to inhibit growth of potentially harmful intestinal pathogens and protect the intestine from the formation of necrotic enteritis in broilers (59). Members of the genus Phyllobacterium are known to have heavy metal resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Butyricicoccus are tolerant to changing intestinal conditions, produce butyrate, and have probiotic potential (57,58). In addition, Butyricicoccus is known to inhibit growth of potentially harmful intestinal pathogens and protect the intestine from the formation of necrotic enteritis in broilers (59). Members of the genus Phyllobacterium are known to have heavy metal resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcaceae represent major butyrate producers. The majority of Ruminococcaceae produce butyrate by carbohydrate fermentation via conversion of two acetyl-CoA molecules into crotonyl-CoA [30,[33][34][35]. In addition, Flavonifractor and Pseudoflavinofractor can produce butyrate also by lysine fermentation or by reduction of succinate.…”
Section: Major Bacterial Taxa Colonising Chicken Intestinal Tractmentioning
confidence: 99%
“…Eeckhaut et al [87] reported that probiotic Butyricicoccus pullicaecorum can prevent NE in the digestive tract of broiler chickens by reducing the number of potentially important pathogens in the caeca and ileum. In our recent study, the intestine samples from Gallipro-or Clostat-supplemented diets were examined and found to show a normal tissue architecture with normal intestinal villi ( Figure 2F) and moderate metaplasia of the intestinal epithelium into goblet cells ( Figure 3G), in addition to a negative control group (Figure 2A).…”
Section: Liver and Intestinal Histopathological Signsmentioning
confidence: 99%